A comparative study on germination of wheat grains with different anthocyanin pigmentation of the pericarp in natural or induced aging - E. I. Gordeeva; O. Y. Shoeva; E. K. Khlestkina (Вавиловский журнал генетики и селекции)
One of promising areas of wheat breeding is the creation of varieties with a high concentration of anthocyanins in the grain for the production of functional food products. Nonetheless, the question of how these compounds aﬀect seed viability after long-term storage has remained unexplored. A comparative study on seed viability was conducted using a set of near-isogenic lines on the background of spring wheat variety Saratovskaya 29. These sister lines carry diﬀerent combinations of recombinant DNA regions (on chromosomes 2A and 7D) containing dominant and recessive alleles at loci Pp3 and Pp-D1 (Pp: Purple pericarp), which determine the anthocyanin color of coleoptiles and of the pericarp. Seeds were germinated on two layers of water-moistened filter paper in a climatic chamber at a constant temperature of 20 °C on a 12-hour daylight cycle. During long-term natural storage of the seeds for up to 9 years in a dry ventilated room in Kraft bags at 20 ± 2 °C, the tested wheat samples experienced a loss of seed germination capacity of ~50 %; anthocyanins were found to not participate in the preservation of germination capacity. Nonetheless, anthocyanins contributed to the preservation of seed viability under unfavorable short-term conditions of a temperature rise to 48 °C at 100 % humidity. The accelerated aging test did not predict poor germination capacity after long-term seed storage. The results showed a neutral role of anthocyanins in the maintenance of seed germination capacity for 6–9 years under natural storage conditions at 20 ± 2 °C. A small statistically significant increase in grain germination capacity during natural aging was associated with the presence of a recombinant region containing the Pp-D1 gene on wheat chromosome 7D.